Ochronosis Presenting as Methemoglobinemia. Issue 3 (19th September 2018) - Hugar, Sarah B.; Shulman, Joshua; Yanta, Joseph; Nine, Jeffrey
Abstract: Ochronosis is the blue‐gray discoloration of collagen‐containing tissues due to homogentisic acid (HGA) deposition, secondary to endogenous alkaptonuria or exogenous enzyme inhibition. In renal disease, accumulation of HGA in serum can cause methemoglobinemia. A 60‐year‐old woman with renal disease and anemia presented with 3 days of weakness and months of gray skin discoloration. Her hemoglobin was 8.1g/dl with 24.5% methemoglobin. Despite treatment with methylene blue, exchange transfusion, and continuous renal replacement therapy, the patient died. Autopsy revealed gray discoloration and ochronotic pigment in the ribs and cartilage. Based on these findings, the patient was diagnosed with ochronosis, suggestive of alkaptonuria, complicated by methemoglobinemia. The differential diagnosis for blue‐gray skin discoloration includes argyria, methemoglobinemia, and ochronosis. This patient's clinical and autopsy findings suggested alkaptonuria complicated by methemoglobinemia due to progressive renal dysfunction. Development of methemoglobinemia in the setting of chronic skin discoloration and renal failure should prompt consideration of alkaptonuria.